\(\sqrt{9-x^2}\)

">
K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

1 tháng 12 2021

\(ĐKXĐ:9-x^2\ge0\Leftrightarrow x^2\le9\Leftrightarrow-3\le x\le3\)

1 tháng 12 2021

−3 ≤ x ≤ 3

7 tháng 6 2019

1) \(\frac{1}{\sqrt{2x-1}}\)có nghĩa khi \(\hept{\begin{cases}2x-1\ge0\\\sqrt{2x-1}\ne0\end{cases}}\)

\(\Leftrightarrow2x-1>0\)

\(\Leftrightarrow x>\frac{1}{2}\)

\(\sqrt{5-x}\)có nghĩa khi \(5-x\ge0\Leftrightarrow x\ge5\)

Vậy \(ĐKXĐ:\frac{1}{2}>x\ge5\)

2) \(\sqrt{x-\frac{1}{x}}\)có nghĩa khi \(\hept{\begin{cases}x-\frac{1}{x}\ge0\\x>0\end{cases}}\)

\(\Leftrightarrow\hept{\begin{cases}\frac{x^2}{x}-\frac{1}{x}\ge0\\x>0\end{cases}}\)

\(\Leftrightarrow\hept{\begin{cases}\frac{x^2-1}{x}\ge0\\x>0\end{cases}}\)

\(\Leftrightarrow\hept{\begin{cases}x^2-1\ge0\\x>0\end{cases}}\)

\(\Leftrightarrow\hept{\begin{cases}x^2\ge1\\x>0\end{cases}}\)

Vậy \(ĐKXĐ:x\ge1\)

3) \(\sqrt{2x-1}\)có nghĩa khi \(2x-1\ge0\) \(\Leftrightarrow x\ge\frac{1}{2}\)

\(\sqrt{4-x^2}\)có nghĩa khi \(4-x^2\ge0\Leftrightarrow x^2\le4\Leftrightarrow x\le2\)

Vậy \(ĐKXĐ:\frac{1}{2}\le x\le2\)

4) \(\sqrt{x^2-1}\)có nghĩa khi \(x^2-1\ge0\Leftrightarrow x^2\ge1\Leftrightarrow x\ge1\)

\(\sqrt{9-x^2}\)có nghĩa khi \(9-x^2\ge0\Leftrightarrow x^2\le9\Leftrightarrow x\le3\)

Vậy \(ĐKXĐ:1\le x\le3\)

30 tháng 9 2019

Tìm ĐKXĐ:

a)\(\frac{\sqrt{2x+4}}{\sqrt{x^2-6x+9}}\)

ĐKXĐ:\(x>0;x\ne3\)

b)\(\frac{x+2}{\sqrt{x^2+4}}\)

ĐKXĐ:\(x>0\)

c)\(\frac{\sqrt{2+x}}{\sqrt{1-x}}\)

ĐKXĐ:\(x>0;x\ne1\)

19 tháng 7 2018

\(\frac{9-4}{x-3}\ge0\)

\(x>3\)

có j sai xót mong m.n bỏ qua

a: ĐKXĐ: (x-1)(x-3)>=0

=>x>=3 hoặc x<=1

b: ĐKXĐ: \(\left\{{}\begin{matrix}x-2\ge0\\4-x\le0\end{matrix}\right.\Leftrightarrow2\le x\le4\)

c: ĐKXĐ:\(\left\{{}\begin{matrix}x^2-4\ge0\\x-2\ge0\end{matrix}\right.\Leftrightarrow x\ge2\)

d: ĐKXĐ: \(\left\{{}\begin{matrix}x+3\ge0\\x^2-9\ge0\end{matrix}\right.\Leftrightarrow\left\{{}\begin{matrix}x\in[-3;+\infty)\\x\in(-\infty;-3]\cup[3;+\infty)\end{matrix}\right.\Leftrightarrow x=-3\)

24 tháng 8 2020

mình giúp bài 3 cho 

\(\sqrt{25x-125}-3\sqrt{\frac{x-5}{9}}-\frac{1}{3}\sqrt{9x-45}=6\left(ĐKXĐ:x\ge5\right)\)

\(< =>\sqrt{25\left(x-5\right)}-3\sqrt{\frac{x-5}{9}}-\frac{1}{3}\sqrt{9\left(x-5\right)}=6\)

\(< =>\sqrt{25}.\sqrt{x-5}-3\frac{\sqrt{x-5}}{\sqrt{9}}-\frac{1}{3}\sqrt{9}.\sqrt{x-5}=6\)

\(< =>5.\sqrt{x-5}-3.\frac{\sqrt{x-5}}{3}-\frac{1}{3}.3.\sqrt{x-5}=6\)

\(< =>5.\sqrt{x-5}-\sqrt{x-5}-\sqrt{x-5}=6\)

\(< =>3\sqrt{x-5}=6< =>\sqrt{x-5}=2\)

\(< =>x-5=4< =>x=4+5=9\left(tmđk\right)\)